2014
DOI: 10.1007/s40093-014-0058-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effects of earthworm Eisenia fetida-based products on the pathogenicity of root-knot nematode (Meloidogyne javanica) infecting cucumber

Abstract: Background Biocontrol of nematode agents to decrease the hazardous impacts of chemical pesticide application including problems of public health and environmental pollution is a priority. In this study, solid (Vermicompost) and liquid products (Liquid Vermicompost, Vermiwash and Coelomic fluid) of the earthworm species Eisenia fetida were tested against root-knot nematode, Meloidogyne javanica in vitro and greenhouse conditions. Results Results showed that Liquid Vermicompost, Coelomic fluid and Vermiwash had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 15 publications
2
12
0
1
Order By: Relevance
“…Yardim et al [26] reported reduction in the Manduca quinquemaculata, Acalymma vittatum, and Diabotrica undecimpunctata infestations in the cucumber and tomato plants grown in pig manure VC. Several other reports also suggest that VC amendment significantly reduces pathogen attacks on plants [90][91][92][93][94][95][96].…”
Section: Effect Of Vermicompost On Pests and Diseasementioning
confidence: 97%
See 1 more Smart Citation
“…Yardim et al [26] reported reduction in the Manduca quinquemaculata, Acalymma vittatum, and Diabotrica undecimpunctata infestations in the cucumber and tomato plants grown in pig manure VC. Several other reports also suggest that VC amendment significantly reduces pathogen attacks on plants [90][91][92][93][94][95][96].…”
Section: Effect Of Vermicompost On Pests and Diseasementioning
confidence: 97%
“…Increased secondary defense compounds, related gene expression, plant growth and the changes of soil properties particularly the increase of pH, IAA and microbial activity. [96] Not stated Walnut (Juglans regia) Agrobacterium tumefaciens Biotic nature [298] Cow dung Mung bean (Vigna radiata) Macrophomina phaseolina Microbial activity [188] Not stated Cucumber (C. sativus) Meloidogyne javanica Hydrogen sulfide, ammonium and nitrates and rhizobacteria accumulation around the plant roots [95] Beneficial microflora, production and release of allelochemicals [301] Not stated Cucumber (C. sativus) Aphis gossypii Microbial activity [302] Not stated Curly bamboo (Dracaena sanderiana) Erwinia spp. Soil borne microbes [303] Food waste Corn (Zea mays) Helicoverpa zea Microbial activity [94] Medical plant wastes and cattle manure Potato (Solanum tuberosum) Globodera rostochiensis and G. pallida Ammonium content [304] Animal manure and agro wastes Tomato (L. esculentum) Pratylenchus spp.…”
Section: Meloidogyne Incognitamentioning
confidence: 99%
“…Entretanto, foi testada neste estudo devido a possibilidade de ocorrer maior biodisponibilidade no solo dos compostos nematicidas, nutrientes e demais substâncias estimuladoras do crescimento disponibilizados pelos adubos orgânicos (ROSTAMI et al, 2014). No entanto, não foi verificado incremento nos parâmetros avaliados.…”
Section: Resultsunclassified
“…The decomposer bacteria reported to win the pathogenic bacteria in competition and in the place where decomposers bacteria are there, the disease-causing bacteria cannot survive. The decomposer bacterias in the gut of earthworms and in drilosphere were able to suppress pathogenic bacteria, which could cause disease to soil animals and plants ( Rostami et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…A study was carried out on application of vermiwash, liquid vermicompost, and coelomic fluid extracted from earthworm Eisenia fetida to control root-knot nematode ( Meloidogyne javanica ) in vitro and under greenhouse conditions ( Rostami et al, 2014 ). The results showed that the three products (vermicompost, coelomic fluid, and vermiwash) had the highest effect on egg hatching inhibition respectively.…”
Section: Methodsmentioning
confidence: 99%